Power output in the jump squat in adolescent male athletes - Dayne, A.; Dayne, A. M.; Nuzzo, J. L.; McBride, J. M.; Burr, A.; Triplett, T. N. (The Journal of Strength and Conditioning Research, 2010)
Previous investigations have examined power output in the jump squat in college-age subjects and it has been determined that the load at which jump squat peak power is maximized in this population is body mass. No data exists in the adolescent population. Additionally, few studies have examined the possible relationship between one repetition maximum (1RM) strength and the load which maximizes peak power. To (1) determine the load at which maximal power output is achieved in the jump squat (JS) in adolescent male athletes and (2) to determine if that load is related to strength-to-body mass ratios. Eleven high school male athletes (age = 15.63 +/- 0.52 years; height = 177.39 +/- 4.93 cm; mass = 80.55 +/- 16.39 kg; squat 1RM = 141.14 +/- 28.08 kg; squat 1 RM-to-body mass ratio = 1.76 +/- 0.15) performed JS testing at loads equal to 0% (body mass), 20%, 40%, 60%, and 80% of individual's squat 1RM. The combination of two linear position transducers and a force plate were utilized to determine peak power (PP), peak force (PF), peak velocity (PV), and peak displacement (PD) at each load. JS at 0% of 1 RM produced significantly higher PP (5162.10 +/- 757.26 W), PV (3.33 +/- 0.34 m/s), and PD (0.46 +/- 0.15 m) in comparison to the 40%, 60%, and 80% of 1 RM loading conditions (p < 0.05). This is the first study to examine power output in adolescent athletes in the jump squat. As concluded in previous studies, power in the JS is maximized at body mass, including adolescent male subjects. It was observed that peak power was attained at body mass regardless of subjects' baseline strength levels. It is evident that lower-body power exercises such as the JS can be performed when training adolescent athletes. An athlete's baseline strength level does not affect the load at which power output is maximized. While it may be beneficial to train at various loads across the loading spectrum, emphasis may be placed on body mass JS when training to optimize power.